Unplanned cesarean sections in advanced maternal age: A predictive model - Joyce Veenstra; Zoë Cohen; Fleurisca J. Korteweg; David P. van derHam; Simone M. Kuppens; Janna A. Kroese; Brenda B. Hermsen; Marije M. Kamphuis; Joost W. Vanhommerig; Maria G. vanPampus (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction As maternal age during pregnancy is rising all over the world, there is a growing need for prognostic factors that determine maternal and perinatal outcomes in older women. Material and methods This study is a retrospective cohort study of women aged 40 years or older at the time of delivery in four Santeon hospitals across the Netherlands between January 2016 and December 2019. Outcomes were compared between women of 40–44 years (advanced maternal age) and 45 years and older (very advanced maternal age). Primary outcome was unplanned cesarean section, secondary outcomes included postpartum hemorrhage and neonatal outcomes. Multivariate regression analysis was performed to analyze predictive factors for unplanned cesarean sections in women who attempted vaginal delivery. Subsequently, a predictive model and risk scores were constructed to predict unplanned cesarean section. Results A cohort of 1660 women was analyzed; mean maternal age was 41.4 years, 4.8% of the women were 45 years and older. In both groups, more than half of the women had not delivered vaginally before. Unplanned cesarean sections were performed in 21.1% of the deliveries in advanced maternal age and in 29.1% in very advanced maternal age. Four predictive factors were significantly correlated with unplanned cesarean sections: higher body mass index (BMI), no previous vaginal delivery, spontaneous start of delivery and number of days needed for cervical priming. A predictive model was constructed from these factors with an area under the curve of 0.75 (95% confidence interval 0.72–0.78). A sensitivity analysis in nulliparous women proved that BMI, days of cervical priming, age, and gestational age were risk factors, whereas spontaneous start of delivery and induction were protective factors. There was one occurrence of neonatal death. Conclusions Women of advanced maternal age and those of very advanced maternal age have a higher chance of having an unplanned cesarean section compared to the general obstetric population in the Netherlands. Unplanned cesarean sections can be predicted through use of our predictive model. Risk increases with higher BMI, no previous vaginal delivery, and increasing number of days needed for cervical priming, whereas spontaneous start of labor lowers the risk. In nulliparous women, age and gestational age also increase risk, but induction lowers the risk of having an unplanned cesarean section.